Metabolic profile comparison of fruit juice from certified sweet cherry trees (Prunus avium L.) of Ferrovia and Giorgia cultivars: A preliminary study. (December 2016) - Girelli, Chiara Roberta; De Pascali, Sandra Angelica; Del Coco, Laura; Fanizzi, Francesco Paolo
Abstract: Sweet cherries are widely appreciated for fresh consumption as well as for production of juices, jams, jelly fruits and alcoholic beverages. The sweet cherry intake (as fresh fruit and related products) is extensively encouraged for their taste and nutritional qualities, due to the presence of water-soluble (C, B) and fat-soluble (A, E and K) vitamins, carotenoids, polyphenols and minerals, as well as glucose and fructose. However the market often endorses the consumption of a particular sweet cherry cultivar (as for most of vegetables) essentially for organoleptic and/or external appearance rather than nutraceutical qualities. In order to evaluate the potential difference in the nutritional quality of fruits, 56 sweet cherry juice samples from certified trees ( Prunus avium L.) of two cultivars (30 from Ferrovia and 26 from Giorgia), grown in the same pedoclimatic Apulian region, were analyzed by 1 H NMR spectroscopy and Multivariate Analysis (MVA). Interestingly, despite the usually lower commercial value with respect to the Ferrovia, Giorgia cultivar shows higher content of malic acid and phenolic compounds with important well known nutraceutical properties such as antioxidant activity and stimulating metabolism. Graphical abstract: An untargeted 1 H NMR based MVA comparison of the metabolic profiles of two typical Apulian sweet cherry cultivars, Ferrovia and Giorgia. Highlights: 1 H NMR based MVA comparison of Ferrovia and Giorgia cherry cultivars was performed. Giorgia shows higher content of organic acids and antioxidant phenolic compounds. 1 H NMR and MVA offer a fast reliable tool for fruit nutraceutical content comparison.